Morphology, morphometry, and phylogeny of the protozoan parasite, Eimeria labbeana-like (Apicomplexa, Eimeriidae), infecting Columba livia domestica - Albasyouni, Shurug; Abdel-Gaber, Rewaida; Al Quraishy, Saleh; Al-Shaebi, Esam M.; Mohammed, Osama B. (Frontiers in Veterinary Science, 2024)
Introduction Eimeria spp. are intracellular protozoan parasites of the phylum Apicomplexa causing economic losses to various wild and domestic animals. An eimerian species infecting Columba livia domestica was identified in this study. Methods A total of 15 faecal samples were examined by floatation technique, a prevalence rate of 60% was reported. Eimerian oocysts were sporulated in 2.5% potassium dichromate solution then identified using morphological and molecular (DNA amplification of the 18S rRNA and ITS-1 genes) diagnostic techniques. Results Sporulated oocysts were identified as Eimeria labbeana-like, after morphometry with typical bi-layered wall with spherical to subspherical oocysts morphology. A polar granule is present, but no micropyle or oocyst residuum. Sporocysts are elongated ovoidal with stieda body. Sporocyst residuum with many granules and sporozoites with refractile bodies and nucleus. Both 18S rRNA and ITS-1 sequences have been deposited in GenBank database. DNA sequences from the partial 18S rRNA generated from the oocysts were found to be related to eimerian and isosporan parasites found in domestic pigeons. For the first time, ITS-1 sequences for E. labbeana-like were provided. Conclusion The necessity of using molecular techniques to describe pigeon intestinal coccidian parasites in conjunction with traditional morphology-based tools was emphasized in this work in order to understand the biology of such parasites.